Porous membranes from acid decorated block copolymer nano-objects via RAFT alcoholic dispersion polymerization. Issue 10 (4th February 2016) - Upadhyaya, Lakshmeesha; Semsarilar, Mona; Fernández-Pacheco, Rodrigo; Martinez, Gema; Mallada, Reyes; Deratani, André; Quemener, Damien
Abstract : Acid decorated diblock copolymer nano-objects were prepared by polymerization-induced self-assembly via RAFT dispersion polymerization of methyl methacrylate. Spheres were used to prepare thin film membranes. Abstract : The RAFT dispersion polymerization of methyl methacrylate (MMA) was conducted in ethanol at 70 °C using a poly(methacrylic acid) (PMAA) chain transfer agent. The poly(methacrylic acid) block is soluble in ethanol and acts as a steric stabilizer for the growing insoluble PMMA chains, resulting in the in situ formation of diblock copolymer nano-objects (Polymerization Induced Self-Assembly (PISA)) in the form of spheres, worms or vesicles, depending on the precise reaction conditions as judged by transmission electron microscopy and dynamic light scattering studies. Two detailed phase diagrams using PMAA27 and PMAA47 macro-CTAs were constructed as a road map for the synthesis of pure morphologies. It was observed that the pure phases could be obtained using the longer macro-CTA while the pure worm phase was not observed with the shorter PMAA. Spin-coated thin films of the prepared spherical particles exhibited a connected porous network as evaluated by electron microscopy (SEM, TEM). Finally, the prepared porous thin film was tested as an isoporous membrane for water filtration.